2020
DOI: 10.1111/mam.12183
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of environmental DNA metabarcoding for monitoring Neotropical mammals: a case study in the Amazon and Atlantic Forest, Brazil

Abstract: The application of environmental DNA (eDNA) metabarcoding as a biomonitoring tool has greatly increased, but studies have focused on temperate aquatic macro-organisms. We apply eDNA metabarcoding to detecting the mammalian community in two high-biodiversity regions of Brazil: the Amazon and Atlantic Forests. We identified Critically Endangered and Endangered mammalian species and found overlap with species identified via camera trapping. We highlight the potential for using eDNA monitoring for mammals in biodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 18 publications
2
49
0
1
Order By: Relevance
“…At present, we would recommend the use of eDNA metabarcoding alongside other non‐invasive surveying methods (e.g. camera traps) when monitoring invasive species or species of conservation concern to maximize monitoring efforts (Abrams et al, ; Sales, Kaizer, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, we would recommend the use of eDNA metabarcoding alongside other non‐invasive surveying methods (e.g. camera traps) when monitoring invasive species or species of conservation concern to maximize monitoring efforts (Abrams et al, ; Sales, Kaizer, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…What has become apparent from studies in lentic systems (ponds and lakes) is that semi‐aquatic and terrestrial mammals can also be detected (Hänfling et al, ; Harper et al, ). As a result, there has been an increasing focus on the use of both vertebrate (Harper et al, ) and mammal‐specific primer sets (Leempoel, Herbert, & Hadly, ; Sales, Kaizer, et al, ; Ushio et al, ) for detecting mammalian communities using eDNA metabarcoding.…”
Section: Introductionmentioning
confidence: 99%
“…To validate the possible detection of terrestrial mammals from eDNA in their habitats, Ushio et al (2017) developed a universal primer pair (MiMammal, a modified version of MiFish primers) for metabarcoding mammalian eDNA and then tested its performance using water samples from zoo cages and natural water samples from forest ponds. Using MiMammal primers, these authors successfully detected mammals reared in the zoo and representative mammals in the forest from those samples, and subsequent studies demonstrated that MiMammal primers were useful for detecting tropical forest mammals from a natural saltlick (Ishige et al 2017), Neotropical mammals from the Amazon and Atlantic Forest in Brazil (Sales et al 2020a), forest mammals from Jasper Ridge Biological Preserve, California (Leempoel et al 2020), and mammal species in snow tracks during winter in Kyoto, Japan (Kinoshita et al 2019). To the best of our knowledge, MiMammal primers have not been used to detect marine mammals, partly because most of the species identified by the marine mammal visual surveys have been detected with MiFish primers (Closek et al 2019), and Closek et al (2019) stated that MiMammal primers can be used in future studies.…”
Section: Application Of Mifish Edna Metabarcoding To Other Organismsmentioning
confidence: 99%
“…DNA metabarcoding from environmental samples has the potential to be used as an early warning system for the detection of invasive non‐native species, can be used for continuous monitoring programmes, and has been extensively applied for tracking biological invasions in aquatic ecosystems (Deiner et al ). eDNA metabarcoding studies targeting mammalian communities were relatively rare in comparison with other taxonomic groups (Sales et al ), but this may change now that there are established metabarcoding protocols for detecting and monitoring whole communities using vertebrate (Harper et al ) or mammal‐specific primer sets (Ushio et al , Sales et al , b).…”
Section: Detection and Monitoringmentioning
confidence: 99%
“…It is therefore essential that specialised eDNA laboratory facilities (akin to working with ancient DNA) are used (Zinger et al ). Another consideration is the existence of gaps in customised or online reference databases for identifying sequences to the appropriate species level in under‐studied geographic regions (Sales et al ). However, with a carefully planned experimental design and the appropriate field and laboratory controls (Zinger et al ), eDNA metabarcoding has the potential to be applied for early detection and ongoing surveillance of invasive mammals (Harper et al , Sales et al ).…”
Section: Detection and Monitoringmentioning
confidence: 99%